The first step is to multiply so write the equation as 6(x+7)-20=6x and then jump 6 into the box giving you 6x+7. Jump 6 into the other side and get 42 giving you 6x+42-20=6x. Combined like terms 42-20=22. Rewrite the equation as 6x+22=6x than to get the x value one side of the equation. You would bring down the 6x on the left hand side of the problem and transfer it to the right hand side turning its value into a negative -6x. Rewrite the equation 22=6x-6x this will give you 22=0 which is a false statement.

No

D/dx (y6-6x) (7+x45) (5x4)

- 20 = - 4x - 6x

6(x+7)-20=6x

We will use the distributive property to change 6(x+7) into 6x + 6×7.

6x + 42-20=6x

Now we will subtract 20 from 42 to get 22.

6x + 22=6x

Now we will subtract 22 from both sides of the equation.

6x=6x-22

Now we will subtract 5x from both sides of the equation.

X=x-22

This is obviously a false equation.

We will use the distributive property to change 6(x+7) into 6x + 6×7.

6x + 42-20=6x

Now we will subtract 20 from 42 to get 22.

6x + 22=6x

Now we will subtract 22 from both sides of the equation.

6x=6x-22

Now we will subtract 5x from both sides of the equation.

X=x-22

This is obviously a false equation.

This equation doesn't have an answer as such:

6(x +7) - 20 = 6x

6x + 42 -20 = 6x

6x + 22 = 6x

6x - 6x +22 = 0

22 = 0

So the eqaution is incorrect

6(x +7) - 20 = 6x

6x + 42 -20 = 6x

6x + 22 = 6x

6x - 6x +22 = 0

22 = 0

So the eqaution is incorrect